Lean Manufacturing, Agile Strategies, and Their Impact on Efficiency: A Critical Systematic Literature Review - Novriyanto; Cokorda Gede Govinda Partha (The Journal of Management, Digital Business, and Entrepreneurship, 2026)
This research critically examines the application of lean manufacturing and agile strategies in improving operational efficiency across various industries. Using a systematic literature review methodology, a total of 23 articles published between 2017 and 2024 were analyzed. This research systematically investigates the role of lean manufacturing and agile strategies in improving operational efficiency and the adoption of agile strategies in the manufacturing sector. Key findings include the application of lean tools such as 5S, Kaizen, and Total Productive Maintenance (TPM) to reduce waste and increase workplace efficiency. Additionally, the emergence of digital supply chain tools and e-Lean systems is identified as a significant trend in integrating agile methodologies into manufacturing processes. This analysis highlights the transformative impact of lean practices on operational efficiency, as well as the explicit mention of agile strategies—such as Just-in-Time (JIT) and digital standardization—in addressing industry challenges. This review provides actionable insights into the development of lean and agile methods and offers a foundation for further research and practical application in manufacturing.